High-quality development of virtual reality industry from the perspective of environmental regulation - Zhang, Liping; Yang, Yi; Xiong, Kaiqi (Frontiers in Psychology, 2022)
From the perspective of environmental regulation, this paper constructed a high-quality development evaluation system for the virtual reality industry, calculated the high-quality development level of the virtual reality industry, and empirically studied the path of high-quality development of the virtual reality industry based on the research methods of entropy weight method and SEM, as well as the data of listed companies of virtual reality industry in China from 2011 to 2020. The results showed that: the virtual reality industry adapted to the high-quality development level, but there was a certain gap, and the gap was divergent; the degree of corporate public welfare development had a positive effect on corporate profitability, while the degree of green development and coordinated development had a weak impact on corporate profitability. The dimension of public welfare had a reverse effect on the profitability of enterprises. Based on the perspective of environmental regulation, enterprises should avoid environmental costs to enhance their competitiveness, and build an industry chain, technology chain, and value chain to promote the healthy development of the virtual reality industry.